Bounds for q-integrals of ... with applications - He, Zhefei; Wang, Mingjin; Xi, Gaowen (Journal of inequalities and applications, 2015)
(ProQuest: ... denotes formulae and/or non-USASCII text omitted; see image).In this paper, we establish an inequality for the q-integral of the bilateral basic hypergeometric function ... As applications of the inequality, we give some sufficient conditions for the convergence of q-series.